Stiffness after Total Knee Arthroplasty - Manrique, Jorge; Gomez, Miguel M.; Parvizi, Javad (The Journal of Knee Surgery, 2015)
Stiffness after total knee arthroplasty (TKA) adversely affects outcome and impacts patient function. Various risk factors for stiffness after TKA have been identified, including reduced preoperative knee range of motion, history of prior knee surgery, etiology of arthritis, incorrect positioning or oversizing of components, and incorrect gap balancing. Mechanical and associated causes, such as infection, arthrofibrosis, complex regional pain syndrome, and heterotopic ossification, secondary gain issues have also been identified. Management of stiffness following TKA can be challenging. The condition needs to be assessed and treated in a staged manner. A nonsurgical approach is the first step. Manipulation under anesthesia may be considered within the first 3 months after the index TKA, if physical therapy fails to improve the range of motion. Beyond this point, consideration should be given to surgical intervention such as lysis of adhesions, either arthroscopically or by open arthrotomy. If the cause of stiffness is deemed to be surgical error, such as component malpositioning, revision arthroplasty is indicated. The purpose of this article is to evaluate the various aspects of management of stiffness after TKA.
Keywords: arthroplasty; replacement; knee; contracture; joint deformities; acquired; reoperation